Artificial Cells: Toward Artificial Cells: Novel Advances in Energy Conversion and Cellular Motility (Adv. Funct. Mater. 11/2020). (10th March 2020) - Jeong, Sungwoo; Nguyen, Huong Thanh; Kim, Chang Ho; Ly, Mai Nguyet; Shin, Kwanwoo
Abstract : Building a cell de novo, by assembling the core biological elements in a cell‐like space step by step, and mimicking the structure and functions of a living cell has been a long‐standing goal to scientifically understand the mystery of life. In article number 1907182, Kwanwoo Shin and co‐workers introduce the recent advances in the bottom‐up approach to building cell‐mimicking systems, implementing metabolic reactions and motility in artificial cells.